Surface-enhanced spectroscopy: Toward practical analysis probe. Issue 2 (7th February 2019) - Mun, Jungho; Lee, Dasol; So, Sunae; Badloe, Trevon; Rho, Junsuk
ABSTRACT: Surface-enhanced spectroscopy (SES) is a consequence of extreme electromagnetic fields and chemical interactions near a surface. SES is highly sensitive and selective and has been exploited in chemistry, physics, biology, and medicine. It is a rapidly developing technique and is expected to become an important analysis tool. This review introduces theories and concepts of SES techniques including surface-enhanced (SE) Raman scattering, SE infrared absorption, SE chiroptical spectroscopy, and SE fluorescence. Then recent research and applications are discussed to indicate current challenges and future directions.